Social psychiatry in a rapidly changing world - Thomas K. J. Craig (Indian Journal of Social Psychiatry, 2016)
Many societies around the world are experiencing a period of unprecedented change in traditional social roles and customs. Globalisation has contributed to materialism and a me-first individualism that heightens awareness of income inequality that itself is one of the most robust markers of unhappiness in society. Ever increasing urbanisation has driven an erosion of large ‘joint’ family arrangements to be replaced by smaller and relatively isolated nuclear families and single parent living. Mass migration has unmasked deep seated fear and prejudice towards the outsider in society. These global changes are fertile ground for the social conditions that have long been known to be risks for mental illness – poverty, poor quality child care, social isolation and the active discrimination and exclusion of the alien, the physically disabled and mentally ill. While there is little we can do to reverse global change, there is much a social psychiatrist can do to mitigate the effect, ensuring his/her voice is added to other calls for reducing discriminatory practice, promoting evidence-based social interventions such as parenting advice and peer support and ensuring that the success of a treatment is measured not just in terms of symptomatic improvement but in whether it results in an outcome that is valued by the patient.